Potensi Desa Cisambeng Sebagai Daya Tarik Wisata Gastronomi di Kecamatan Palasah Kabupaten Majalengka - Muttaqien, Raden Rizki; Fitrinty, Rattikah (STIEPAR YAPARI Bandung, 2024)
Majalengka Regency has strong tourism development potential in the field of food producers, one of which is located in Cisambeng Village, Palasah District, Majalengka Regency. Being one of the production centers of tofu, tempeh and oncom which is the livelihood of 85% of its residents, Cisambeng Village began to improve in an effort to improve facilities and infrastructure to support gastronomic tourism in Majalengka Regency. Gastronomic tourism is the right strategy in developing the tourism industry in Majalengka Regency. In supporting an area to become a gastronomic city, collaboration between stakeholders called Nona helix (nine springs) is needed . Nona helix consists of entrepreneurs, governments, workers, suppliers, experts, observers, connoisseurs, non-governmental organizations (NGOs) and information technology. This study explains the appropriate form of gastronomic tourism development to be carried out in Cisambeng Village, using qualitative descriptive research methods, with research data obtained from in-depth interviews, observations, and literature studies. The ins and outs of the process of making food and beverage products in accordance with the local cultural values of Cisambeng Village must be able to be packaged into a tourism product that provides its own experience for tourists to visit Cisambeng Village, Majalengka Regency. In addition, support from stakeholders, especially related agencies, namely the Tourism Office and the Industry and Trade Office is needed, not only empowering tempeh and tofu business actors but also monitoring for the success of gastronomic tourism development in Majalengka Regency.